Change Is Here: ADEA CCI 2.0—A Learning Community for the Advancement of Dental Education. Issue 6 (1st June 2017) - Palatta, Anthony M.; Kassebaum, Denise K.; Gadbury-Amyot, Cynthia C.; Karimbux, Nadeem Y.; Licari, Frank W.; Nadershahi, Nader A.; Walji, Muhammad F.; Stewart, Jeffery C.B.; Valachovic, Richard W.
Abstract : On May 12, 2005, the inaugural meeting of the American Dental Education Association Commission on Change and Innovation in Dental Education (ADEA CCI) was convened. Comprised of thought leaders representative of dental education and practice, the ADEA CCI published groundbreaking white papers that effectively helped bring dental education across the threshold of the 21st century. Twelve years later, a new ADEA CCI has been convened—ADEA CCI 2.0. The ADEA CCI 2.0 is a broad‐ranging, strategically interconnected, flexible, and multifarious community of stakeholders situated within and across all facets of oral health education and practice. Whereas the first iteration of the ADEA CCI made the case for change regarding revisions of the dental curriculum and learning environment, the ADEA CCI 2.0 will focus on external domains that are having a global impact on the content and delivery of health care and health professions education and, ultimately, how health care benefits people. The principal work of the ADEA CCI 2.0 will be to create educational and implementation resources and opportunities for dental educators to contemplate, investigate, and ultimately define the future needs of their academic dental institutions in this constantly changing world.